Zebularine and trichostatin a sensitized human breast adenocarcinoma cells towards tumour necrosis-factor-related apoptosis inducing ligand (TRAIL)-induced apoptosis - Kong, Wei Yang (2019)
Triple-negative breast cancer (TNBC) is characterised by the absence of hormone receptors (HR) and human epidermal growth factor receptor 2 (HER2). It is highly aggressive and has the worst clinical outcome worldwide. Current TNBC treatment is limited to chemotherapy which causes adverse side effects to patients. Tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) is a promising cancer therapeutic agent due to its selective killing on cancer cells while sparing the normal cells. Nevertheless, human breast adenocarcinoma cells can develop TRAIL resistance. To overcome this problem, combinational therapy is imperative to reverse TRAIL resistance and augment the apoptosis effects towards human breast adenocarcinoma cells. The administration of epigenetic drugs as sensitizers was reported to enhance the TRAIL-mediated apoptosis in cancerous cells. Therefore, this project aimed to investigate the anti-cancer effects of epigenetic drugs zebularine (Zeb) and trichostatin A (TSA) as sensitizers to human breast adenocarcinoma cells towards TRAIL-induced apoptosis (TZT) and this treatment regimen was compared with the natural anti-cancer compound curcumin (Cur) and standard chemotherapeutic drug doxorubicin (Dox).